Risk assessment of dairy value chain in Assam, Northeast India - Grace, Delia; Lapar, Ma. Lucila; Deka, Ram Pratim (2012)
Traditional (informal) milk market accounts for 97 percent of fresh milk supply I Assam and attempts to establish dairy cooperatives have had limited success. In areas with relatively poor market access, these informal markets represent the only market opportunity for dairy farmers. However, widespread concerns about milk safety and quality have led to decision makers and government support services to ignore or penalize the traditional milk sector. A series of studies among milk value chain actors was conducted to better understand the milk sector in Assam, assess the risk to human health posed by the traditional milk sector, and develop an action plan for improving the performance of the traditional milk sector. Key findings of the studies are: (1) most milk samples do not meet microbiological standards; (2) adulteration of milk is widespread but does not appear to represent a risk to human health; (3) milk handling practices are very poor and is associated with low levels of food safety; and (4) only a minority of milk is pasteurized, and while this does reduce the level of bacterial count, it does not guarantee absence of adulteration or compliance with standards. The risk assessment of the dairy supply chain suggests the following key results: (1) the majority of milk sampled in urban Assam did not meet local standards and may present a risk to public health and (2) formal milk outlets are no better than informal milk outlets in terms of the level of compliance with milk quality standards. Opportunities to potentially improve food safety in traditional milk markets are thus possible and the most promising intervention is some form of certification scheme involving training of informal milk vendors in milk handling.